Obesity, risk of diabetes and role of physical activity, exercise training and cardiorespiratory fitness - Carbone, Salvatore; Del Buono, Marco Giuseppe; Ozemek, Cemal; Lavie, Carl J. (Progress in cardiovascular diseases, 2019)
The epidemic of obesity contributes to the burden of type 2 diabetes mellitus (T2DM) in the United States and worldwide. Importantly, obesity is not only preventable but can be treated, particularly with lifestyle modifications to forestall T2DM in those with excess adiposity. The mechanisms linking obesity to T2DM are numerous and involve adipose tissue remodeling as a result of unhealthy behaviors, including unhealthy diet, reduced physical activity (PA) and exercise training (ET), and increased sedentary behaviors. Taken together, these factors markedly reduce cardiorespiratory fitness (CRF), one of the strongest predictors for cardiovascular outcomes and all-cause mortality in the general population, but also in those with T2DM. In this review we describe the mechanisms leading to adipose tissue remodeling resulting in obesity, as well as the mechanisms linking excess adiposity to insulin resistance and, in turn, T2DM. We then present the therapeutic strategies that can be implemented in obesity to prevent T2DM, with a brief discussion on weight loss, and greater emphasis on PA and ET. We finally present the evidence to support the beneficial effects of such strategies in patients with established T2DM and discuss the importance of achieving improvements in CRF in this population to potentially improve clinical outcomes.